Economic fortunes, ethnic divides, and marriage and fertility in Central Asia : Kazakhstan and Kyrgyzstan compared - Agadjanian, Victor (2013)
Declining marriage and fertility rates following the collapse of state socialism have been the subject of numerous studies in Central and Eastern Europe. More recent literature has focused on marriage and fertility dynamics in the period of post-crisis political stabilization and economic growth. However, relatively little research on marriage and fertility has dealt with the Central Asian part of the post-socialist world. We use survey and published data from Kazakhstan and Kyrgyzstan, two multiethnic countries with differing paths of post-crisis recovery, to examine overall and ethnic-specific trends in entry into marriage and fertility. We find that in both countries rates of entry into marriage continued to decline throughout post-crisis years. By contrast, fertility rose, and this rise was greater in the more prosperous Kazakhstan. However, we also detect considerable ethnic variations in fertility trends which we situate within the ethnopolitical and ethnodemographic contexts of both countries.